Giant prostatic hyperplasia and its causes - Anglickis, Marius; Platkevičius, Gediminas; Stulpinas, Rokas; Miklyčiūtė, Lina; Anglickienė, Giedrė; Keina, Vytautas; Štarolis, Edmundas; Gradauskas, Audrius (Acta medica Lituanica, 2020)
We present a case of a 59-year-old male who was admitted to the emergency department with urinary retention, with a history of lower urinary tract symptoms, with the value of serum prostate specific antigen level of 100 ng/mL and an estimated prostate size of 800 mL, according to magnetic resonance imaging. A prostate biopsy showed benign prostatic hyperplasia. Transvesical prostatectomy was performed, following additional procedure of transurethral resection of the prostate. To the best of our knowledge, this is the fourth highest prostate volume reported in medical literature. In this paper, we examine the factors that may have influenced the development of giant prostate hyperplasia.
Keywords: benign prostatic hyperplasia; giant prostatic hyperplasia; prostate; transvesical prostatectomy